PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS XI IPS SMA MAMBA’ UNNUR GADING BULULAWANG, KABUPATEN MALANG - Fitri, Aurina Gita; Abdulloh, Abdulloh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to determine the increase in learning activeness and learning outcomes of students in class XI-IPS SMA Mamba'Unnur Gading in learning Islamic Religious Education and Budi Pekerti by using the STAD type cooperative learning model. This research is a type of Classroom Action Research (PTK), with the research subject being 16 students of class XI IPS SMA Mamba Unnur Gading. The data collection technique used test and observation methods. The results showed that there was an increase in the activeness and learning outcomes of XI-IPS class students in Islamic Religion and Budi Pekerti lessons which are described as follows: In the pre-cycle period the level of learning activeness and student learning completeness was only at a percentage of 37.5% and 31.25%. In cycle I, the level of learning activeness and learning completeness was presented as 70% and 68.75%, while in cycle II, the level of learning activeness and learning completeness reached a percentage of 85% and 87%, which indicates that this class action research is considered successful.